The incidence of avascular necrosis in children with cerebral palsy after hip containment surgery. (December 2022) - Bauer, Jeremy P; Sienko, Susan; Roy, Dennis; Nye, Deric; Tarrant, Seth; Price, Ryan; Raney, Ellen
Purpose: To establish the rate of avascular necrosis after hip reconstruction surgery in children with cerebral palsy and to identify risk factors that influence the development of avascular necrosis in this population. Methods: An institutional review board–approved retrospective review was conducted on children with cerebral palsy who underwent hip containment surgery at a single institution. Radiographs were evaluated at three time points. The Reimer's migration percentage, neck shaft angle, epiphyseal shaft angle, acetabular index, center edge angle, and acetabular angle were measured. The presence of avascular necrosis was evaluated and graded by the Bucholz/Ogden and the Kalamchi/MacEwen classification systems. Multivariate logistic regression was performed to identify risk factors associated with the development of avascular necrosis. Results: A total of 154 children with cerebral palsy underwent hip containment surgery on 223 hips. Twenty-nine children (18.8%) underwent both pelvic and femoral procedures; 36 children (23.4%) had only femoral procedures; 47 children (30.5%) had femoral and soft tissue; and 42 children (27.3%) had pelvic, femoral, and soft tissue procedures. Using the Bucholz and Ogden or the Kalamchi classifications, the rate of avascular necrosis was 24.7% (38/154). Of the variables evaluated, preoperative Reimers was found to be significant predictors of avascular necrosis. The rate of avascular necrosis was 26.7% for Gross Motor Functional Classification System level III, 24.1% for Gross Motor Functional Classification System level IV, and 27.3% for Gross Motor Functional Classification System level V. Conclusion: The overall rate of avascular necrosis in children undergoing hip containment surgery was 26.7%. Together, age at surgery, open reduction, previous surgery, preoperative Reimers, and estimated blood loss contributed to the development of postoperative avascular necrosis; however, only preoperative Reimers significantly contributed to the development of avascular necrosis in children with cerebral palsy undergoing hip containment procedures.